Lojalitások és lojalitáskonfliktusok az 1945 utáni vallásos zsidóság életében - Beke Zsolt; Zsidó lojalitáshierarchiák dinamikája a modernkori Közép-Európában (2019) (Szeged) (Néprajzi és Kulturális Antropológiai Tanszék Szeged, 2024)
In the post-World War II period, questions of loyalty within the Hungarian religious Jewish community became particularly complex and multifaceted. The post-Holocaust era brought drastic changes to the lives of both communities and individuals due to the immense losses suffered. Under the new political system, the state closely supervised religious communities and interfered in their internal affairs. Loyalty to the state was often coerced, requiring significant adaptation. Nationalizations and employment difficulties further exacerbated conflicts of loyalty, as religious Jews had to comply with state laws while also meeting the expectations of their religious community. In this new hierarchy of loyalty, the relationship with Israel played a significant role, introducing previously unknown conflicts of allegiance. Despite state intervention and attempts at unification, loyalty conflicts persisted along the Orthodox-Neolog divide. For many, the losses suffered by the community made it impossible to maintain previous criteria of loyalty, leading to changes in identity.
Keywords: Bölcsészettudományok; Történettudomány és régészet